Predator aversion in resident generalist birds. A ghost of evolutionary past? - Hotvedt, Ådne (UiT Norges arktiske universitet, 2018)
Predator aversion is an important adaptation that can significantly lower the mortality rate among prey animals, but avoiding a predator requires knowing and recognizing them. The predator aversion of Common gulls and Mallard ducks at Prestvannet Lake, Tromsø, Northern Norway was tested in an experiment by placing differing objects resembling snakes next to bread during the summer and autumn of 2017. The birds were chosen because they were resident generalists who presumably used to interact with snakes, and now live in environments without them. The time spent before accessing the bait by a rubber snake, a garden hose and a control was used to gauge the fearful response to the treatments in question, with a longer duration implying a higher level of aversion or fear. The resulting data indicated that the common gull’s ability to distinguish between objects was more substantial than that of the mallard duck and that the mallard duck was less sensitive to the differences between treatments. In addition, the presence of a potential predator seemed more influential on bird behavior than bird density and the associated competition between birds.